PURITANISME DALAM GERAKAN TAJDID MUHAMMADIYAH: TELAAH HISTORIS, EPISTEMOLOGIS, DAN SOSIO-KULTURAL - Salsabila, Mira; Nasir, Maigus; Webrizal; Mursal (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study examines the shift from culturalism to puritanism within the Muhammadiyah reform movement using a library research approach. Culturalism, characterized by religious practices rooted in local traditions and communal customs, encounters substantial transformation when confronted with Muhammadiyah’s long-standing agenda of purification and modernization. Through analysis of official documents, scholarly literature, and Muhammadiyah’s doctrinal texts, the study demonstrates that puritanism is not merely a rejection of local culture but an epistemological and institutional project aimed at restructuring religious authority, rationalizing worship, and redefining Islamic identity among Muhammadiyah adherents. This shift is shaped by the modernization of education, the expansion of digital media, social mobility, and increasing exposure to global Islamic discourses. The findings reveal that puritanism functions as a reformist framework that molds contemporary religious practices, authority structures, and organizational identity, while simultaneously generating contestation with existing culturalistic traditions in Indonesian Muslim society. The study contributes to the sociology of religion and Islamic movement studies, particularly regarding the relationship between religion and culture as well as contemporary Islamic reform.